Innate immune activation of swine gastrointestinal epithelial cells and tissues in response to microbial exposure - Skjolaas, Kristine A. (Kansas State University, 2006)
The three experiments described below offer support of immune function by the swine gastrointestinal epithelium. Experiment one evaluated mediators that regulate the movement of macrophages (macrophage migration inhibitory factor; MIF), neutrophils (interleukin 8; IL8), dendritic cells (CC chemokine ligand 20; CCL20) and epithelial remodeling (osteopontin; OPN) in pigs challenged with Salmonella enterica serovar Typhimurium (ST) or Choleraesuis (SC). The proximal ileum had greater IL8 expression than the distal ileum (P < 0.05), and ST increased CCL20 (P < 0.05). In vitro, MIF, IL8, CCL20 and OPN mRNA expression induced by lipopolysaccharide (LPS), ST or SC using pig jejunal epithelial cells (IPEC-J2) resulted in increased IL8 secretion, and increased IL8 and CCL20 mRNA by ST and SC (P < 0.05). Experiment two evaluated how Lactobacillus reuteri (LR) and Bacillus licheniformis (BL) differed from ST or SC in their ability to regulate, stimulate, or modify IL8, CCL20, and tumor necrosis factor α (TNFα) in IPEC-J2 cells. ST stimulated an increase in IL8 secretion, with increases in IL8 mRNA (P < 0.05). BL increased IL8 mRNA (P < 0.0001). CCL20 mRNA was upregulated by ST (P < 0.05) and BL (P < 0.05). Only ST increased TNFα mRNA (P < 0.05). Another objective evaluated whether pre-exposure of IPEC-J2 cells to LR or BL modified ST induced IL8 secretion. IL8 secretion was increased by ST (P < 0.0001), and reduced by LR (P < 0.05). Only the BL/ST co-treated wells blunted basolateral IL8 secretion (P < 0.0001). Experiment three characterized the swine CCL20 mRNA sequence and evaluated tissue expression. Cloning of CCL20 from the porcine jejunum predicted a 97 amino acid peptide. All healthy tissues expressed CCL20 mRNA. In animals challenged with Salmonella spp., SC increased spleen and liver CCL20 expression. The data demonstrate that invasive bacterial pathogens in the pig gastrointestinal tract trigger upregulation of selected proinflammatory mediators; Salmonella spp. elicited differing patterns of activation in vitro and in vivo; IPEC-J2 cells increased IL-8 secretion in response to ST and BL, but not LR, while ST stimulated secretion was inhibited basolaterally by BL pre-exposure; and numerous porcine tissues are prominent sources CCL20.
Keywords: Chemokines; Mucosal immunology; Cytokines; Swine; Salmonella enterica; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Animal Pathology (0476); Biology, Animal Physiology (0433)